Activation and characterization of dune sand as partial cement replacement for concrete - Abdullah, Asiah (2012)
Dune sand obtained in the vicinity of Riyadh, Saudi Arabia has been investigated to be used as partial cement replacement materials for concrete. Physical and chemical properties of dune sand were evaluated and it was found that it has potential to be processed and used as partial cement replacement due to the high silica content of about 93.4%. However, dune sand is inert and chemically inactive under normal condition. Results show that the strength decreases with the increase of cement replacement by dune sand under normal condition. Therefore, different methods have been developed to enhance the reactivity of dune sand. Three ways were used to improve the pozzolanic reactivity including chemical activation, mechanical activation and thermal activation. For chemical activation, four inexpensive materials which are NaCl, Na2SO4, CaSO4·2H2O and CaCl2·2H2O were chosen for this study. Results showed that the addition of chemical activators did not demonstrate an obvious effect on the strength development of the cement. In the mechanical activation, the dune sand with prolonged grinding was investigated to study the effect of using different particle size on the dune sand reactivity. However, it did not result in substantial improvements to strength. For thermal activation, two different techniques were used which are calcination (heat treatment) and autoclave curing. The calcination process was done to activate the raw material of dune sand at temperature ranging from 400oC to 1000°C. Experimental results indicated that the ultimate strength of cement pastes decreased with increasing calcination temperature. The autoclave curing increased the pozzolanic activity of dune sand with significant improvement in strength. The maximum compressive strength was found at 30% replacement of cement by dune sand. The final products obtained were further analyzed by X-ray diffraction (XRD), scanning electron microscope (SEM), differential thermal analysis (DTA) and thermogravimetric analysis (TGA) to investigate the mechanism that caused the increase in the compressive strength. Elimination of Ca(OH)2 peaks in the XRD analysis clearly proved that crystalline SiO2 in dune sand can quickly react with Ca(OH)2 that are formed from cement hydration to form a new type C-S-H hydrate (tobermorite) which improve the strength and concrete structure under autoclave curing. The compressive strength of autoclaved concrete containing 30% dune sand as partial cement replacement increased by 28% compared to concrete that have been subjected to the standard curing after 154 days. Free Ca(OH)2 content was reduced from 26% in control paste under standard curing to about 3% in autoclaved cement paste containing 30% dune sand as partial cement replacement which experienced a reduction of about 89%. DTA results are also in good agreement with findings by TGA showing lower content of free Ca(OH)2 in autoclaved products compared to the standard curing. In general, SEM investigation revealed that the utilization of concrete containing 30% dune sand as partial cement replacement subjected to autoclave curing produced more compact microstructure compared to those cured under normal curing.